ALEXANDER BURNES'S TRIP TO BUKHARA SHARIF AND HIS RELATIONS WITH THE BUKHARA KUSHBEGI (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
In the 19th century, the clash of interests between the Russian Empire and Great Britain in Central Asia created political competition between the two empires. This rivalry led to efforts by both empires to gather valuable information about the area. Therefore, both empires began to send their spies to this region in the guise of travelers, merchants, and travelers. Of course, to embark on such a difficult journey, a traveler must be able, courageous, brave, patient, knowledgeable, and intelligent. One such traveler was Alexander Burnes (1805-1841), a native of Scotland. He was fluent in Persian, Arabic and Hindi. He wrote a work called "Travels into Bokhara," meaning "Journey to Bukhara." In this book he describes the difficulties encountered on the way, the social, political, religious and ethnic events of the peoples, and this book brings Alexander Burnes great fame in Great Britain. This book also contains valuable information about the Bukharan Emirate.